The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1007/bf02859414
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of febrile convulsions

Abstract: A cohort of hundred children with febrile convulsions, in the age group of 3 months to 5 years were followed up prospectively for one year to study the natural course of the illness, and to determine if specific factors would increase the risk of recurrence of febrile convulsions. The risk factors studied were age of onset under one year, long duration of convulsion (more than 15 minutes), family history of febrile convulsion or epilepsy and combination of two or all of the above factors. Four groups of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Pavlidou et al [3] in their study have shown that young age plays a major role in susceptibility of FS, and if there is an individual temperature threshold level above which a [6] showed that children with recurrent seizures were younger at age of onset and had more often family history of FS; and on the whole age less than 16 months at the moment of first convulsion and existence of family history of epilepsy or FS increases the recurrence of FS. Another study in which risk factors of FS were studied including 1) age of onset under one year, 2) long duration of convulsion (more than 15 minutes) and 3) family history of epilepsy or convulsion) showed that although all the groups with risk factors had a trend towards a higher recurrence rate in comparison to controls, difference observed clinically was not statistically significant [7]. In our study, a significant correlation is present between FS and age less than 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Pavlidou et al [3] in their study have shown that young age plays a major role in susceptibility of FS, and if there is an individual temperature threshold level above which a [6] showed that children with recurrent seizures were younger at age of onset and had more often family history of FS; and on the whole age less than 16 months at the moment of first convulsion and existence of family history of epilepsy or FS increases the recurrence of FS. Another study in which risk factors of FS were studied including 1) age of onset under one year, 2) long duration of convulsion (more than 15 minutes) and 3) family history of epilepsy or convulsion) showed that although all the groups with risk factors had a trend towards a higher recurrence rate in comparison to controls, difference observed clinically was not statistically significant [7]. In our study, a significant correlation is present between FS and age less than 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies (Table 3) comparing use of phenobarbital and placebo, in five ones 4,6,[13][14][15] phenobarbital reduced the recurrence risk for febrile seizures. But in 3 studies 4,13-15 , the relative reduced risk was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies demonstrating a relation between the number of febrile seizures, mainly the complex ones, and the risk for epilepsy [2][3] . Besides, recurrent convulsions may be deleterious to intellectual development 4 . The prevention of febrile seizures might be benefi-cial, but the long-term management is controversial [5][6][7] .…”
mentioning
confidence: 99%
“…In addition, it has been used widely prophylactically to prevent recurrence of febrile seizures. Some studies have found that long‐term phenobarbital therapy reduces recurrence after simple or atypical febrile convulsions (Wolf et al., 1977; Camfield et al., 1980; Bacon et al., 1981; Mamelle et al., 1984; Thilothammal et al., 1993), whereas others have found no significant difference when compared to placebo or intermittent diazepam (Knudsen & Vestermark, 1978; Mckinlay & Newton, 1989). Two meta‐analytic reviews concluded that, despite a statistically significant benefit in seizure rate reduction, the heterogeneity of participating studies and side effects did not allow any recommendation for using phenobarbital as long‐term prophylaxis (Rantala et al., 1997; Masuko et al., 2003).…”
Section: Phenobarbital After 1975mentioning
confidence: 99%